Research Report - Repurposing Grape Marc - Jones JR; McLaren S; Chen Q; Seraj M (Marlborough District Council, 2020)
Section 1. Executive Report (page 2) Section 2. Background to the Project (page 25) Section 3. Detail Report - Thermal Processes: Technical and Economic Analysis (page 35) Section 4. Detail Report - Environmental Analysis by Carbon Footprint (page 69)
Keywords: grape marc; thermal processing; biochar; compost